2018
DOI: 10.1186/s13098-018-0322-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index and health and economic outcomes in Brazil

Abstract: BackgroundObesity is associated with significant physical, psychosocial and economic burden globally. In Brazil, almost 50% of the population is either overweight or obese. The prevalence of morbid obesity increased by 255% between 1975 and 2003. The current study sought to quantify the relationship between weight status and health outcomes.MethodsData from three waves (2011, 2012, and 2015) of the Brazil National Health and Wellness Survey, an Internet-based survey administered to a demographically diverse sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…Several studies around the globe also found significant relationships between BMI in the obesity range and work-related limitations including absenteeism and presenteeism. DiBonaventura et al [27], Finkelstein et al [11] and Gates et al [14] examined workers in the US, Bustillos et al [13] for Canada and Kudel et al [28] for Brazil to document the negative impact of BMI or obesity on workplace productivity. This study's findings have several implications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies around the globe also found significant relationships between BMI in the obesity range and work-related limitations including absenteeism and presenteeism. DiBonaventura et al [27], Finkelstein et al [11] and Gates et al [14] examined workers in the US, Bustillos et al [13] for Canada and Kudel et al [28] for Brazil to document the negative impact of BMI or obesity on workplace productivity. This study's findings have several implications.…”
Section: Discussionmentioning
confidence: 99%
“…Severe obesity is occurring globally with increasingly high prevalence [1,2], contributes to reduced functional and health status [3][4][5], and is associated many common medical comorbidities, including type-2 diabetes [6,7], hypertension and cardiovascular disease [8], and sleep disorders [9]. Though less widely recognized by the general public, obesity is also associated with reduced cognitive performance and an increased prevalence of neurocognitive deficits [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, this challenge is still far from being faced. Increased obesity has become a worldwide concern due the costs involved and the subsequent effects on health, reduced life expectancies and high prevalence rates 1,2 . Bariatric surgery has been seen as the main treatment for severe obesity, since it can lead to important weight losses in one year and guarantees that comorbidities are reduced 3 .…”
Section: Introductionmentioning
confidence: 99%